Factors Analisys of the Event of Premature Rupture of Membranes with Mothers in Labor During a Pandemic Covid 19 - Agustyn, Lia; Dinengsih, Sri; Lail, Nurul Husnul (Universitas Islam Lamongan, 2022)
Premature rupture of membranes (PROM) is the rupture of the membranes before delivery. The incidence of PROM in the world is still high, at 50-60%, while in Indonesia, it is around 65%. Various factors cause PROM that needs to be known so that mothers with PROM can be treated appropriately, namely age, parity, education, infection, and history of PROM. This study aimed to determine the frequency distribution and the relationship of age, parity, education, infection, and history of PROM with the incidence of PROM in women giving birth during the Covid-19 pandemic at RS Sentosa Bogor in 2022. This research methodology is analytic observational with a case control research design. The study was conducted at Sentosa Hospital, Bogor, from May to July 2022. This study's population is mothers giving birth at Sentosa Hospital in 2022. The research sample amounted to 108 people with a total sampling technique. The data in the study were carried out by univariate and bivariate analysis using chi-square statistical tests and computerized programs. The results showed that there was a relation between the incidence of PROM in the mother with knowledge (p 0.020), anemia (p 0.015) parity one and >3 (p-value 0.009), infection (p-value 0.037), and history of PROM (p-value 0.005). Meanwhile, there is no relationship between maternal education level (p-value 0.546) and the incidence of PROM in pregnant women. Age, parity, infection, and history of PROM are factors in the occurrence of PROM in pregnant women. It is hoped that there will be counseling for prospective mothers regarding PROM to avoid the occurrence of PROM in pregnant women.